IDENTIFYING GERUNDS AND INFINITIVES BY INDONESIAN EFL LEARNERS: AN ERROR ANALYSIS - Wijaya, Muhammad Hadi (GoAcademica CRP, 2024)
The primary aim of this research is to identify and explore the common errors made by eleventh-grade students at SMKS Bintan Insani in their usage of gerunds and infinitives, as well as to investigate the factors contributing to these errors. This study adopts an analytical approach within the framework of a descriptive quantitative research design to elucidate the nature of the errors made by students. Data collection was achieved through the administration of a written test. Furthermore, to gain a deeper understanding of the factors influencing these errors, open-ended interviews were conducted with the students. Upon completion of the analysis, it was evident that the thirty eleventh-grade students collectively produced a total of 386 errors. Among these errors, 56 (14.51%) were identified as additions, 200 (51.81%) as misformations, and 130 (33.68%) as omissions. These findings underscore the students' limited grasp of gerunds and infinitives, with misformations emerging as the most prevalent error type. This prevalence indicates uncertainty in the correct selection between gerunds and infinitives. The errors in gerunds and infinitives construction can be attributed to various factors, including interference from the students' mother tongue, wherein structures from their native language are applied to English. Overgeneralization of grammatical rules also contributes to these errors. In addition, shortcomings in the teaching process, characterized by inadequate explanations and limited practice opportunities, hinder student progress. To address these issues, it is imperative to provide explicit instruction, raise awareness of verb patterns, and offer extensive practice opportunities coupled with constructive feedback to enhance the students' proficiency in the accurate usage of gerunds and infinitives.